Realizing the promise of digital pathology - McClintock, David (MLO. Medical laboratory observer, 2021)
Shortly after COVID-19 was declared a national emergency in the U.S., the Centers for Medicare & Medicaid Services (CMS) issued a memorandum on March 26, 2020, waiving the pre-pandemic requirement for remote sites to have a CLIA certificate when reviewing histopathology slides for primary diagnosis.1 The U.S. Food and Drug Administration (FDA) soon followed on April 24, 2020, with a guidance document relaxing enforcement policies that effectively allowed the interim use of digital pathology devices intended for"reviewing and reporting of digital pathology slides from remote locations"without a premarket notification submission.2 The guidance covered automated digital image microscopes, whole slide imaging (WSI) systems, image viewing and management software, and digital pathology displays - typically used in healthcare facilities, but also key components for reviewing and reporting of digital pathology slides from remote settings. [...]automated slide imaging can translate into faster, more accurate results and expedited clinical decision-making, resulting in better patient care. [...]WSI technology comprises not just the slide scanner, but also the software applications and server hardware to manage and display images, and in some cases, algorithms to assist the pathologist or technologist with image interpretation. At this early stage, it is also important to determine where you will incorporate slide scanning into the laboratory workflow: before microscopic analysis, after sign-out but before archiving, on demand after archiving, or maybe a combination of these options?